Dissolved copper enrichment in the Gulf of Mexico is driven by freshwater inputs, sedimentary fluxes, and cross-shelf exchange induced by Loop Current eddies - Delgadillo-Hinojosa, Francisco; Félix-Bermúdez, Armando; Torres-Delgado, Eunise Vanessa; Huerta-Diaz, Miguel Angel; Lares, Maria Lucila; Tovar-Sánchez, Antonio; Quijano-del-Olmo, Sandra Laura; Reyes-Bravo, Mauricio Moises (Frontiers in Marine Science, 2025)
In the ocean, copper functions as an essential micronutrient for primary producers but becomes toxic if its concentration exceeds their cellular requirements. The distribution of copper is strongly controlled by external inputs and physical dynamics, especially in marginal seas with benthic, fluvial, or aeolian sources. We present the spatial distribution of dissolved copper (dCu) in a quasi-zonal transect (25° N) spanning the Gulf of Mexico (GoM) from the Loop Current in the east to the continental slope in the west. The dCu profiles off the continental slope were recorded within a decaying anticyclonic Loop Current eddy (LCE) named Nautilus. In contrast, in the central GoM, dCu profiles were measured on the outside of LCE Olympus, which had recently detached from the Loop Current. The vertical distribution of dCu in the Loop Current was similar to that of the Atlantic Ocean, reflecting the origin of the water entering the GoM. High dCu concentrations in the surface waters of the central GoM were associated with dCu-rich freshwater inputs from the Mississippi River that were transported offshore (>400 km) by LCE Olympus. However, we identified a clear gradient of dCu in surface waters, with the dCu concentration increasing towards the region of LCE Nautilus in the western GoM. The vertical profiles of dCu in the LCE Nautilus also exhibited the highest dCu concentrations and were significantly greater than those of the adjacent Atlantic Ocean. This conspicuous enrichment of dCu was attributed to enhanced off-shelf transport by the decaying LCE Nautilus, in addition to benthic inputs from the continental shelf and slope, with atmospheric fluxes at the surface and the remineralization of organic matter in the water column playing minor roles. Our findings demonstrate that the interaction of mesoscale anticyclonic eddies with the continental margin acts as a mechanism for water exchange between the coastal zone and the deep-water region that is capable of shaping the spatial distribution of dCu in the GoM.